Association between GDF5 rs143383 genetic polymorphism and musculoskeletal degenerative diseases susceptibility: a meta-analysis - Xin Huang; Weiyue Zhang; Zengwu Shao (BMC, 2018)
Abstract Background Several studies have assessed the association between GDF5 rs143383 polymorphism and the susceptibility of musculoskeletal degenerative diseases, such as intervertebral disc degeneration (IDD) and osteoarthritis (OA), but the results are inconsistent. The aim of our study was to evaluate the association between them comprehensively. Methods A systematical search was conducted on PubMed, Scopus, Web of Science (WOS), Embase, and the Cochrane Library databases updated to April 20, 2018. Eligible studies about polymorphisms in GDF5 gene and risk of IDD or OA were included. Pooled odds ratios (ORs) and 95% confidence intervals (95% CIs) were utilized. Results Fifteen studies with a total of 5915 cases and 12,252 controls were finally included in our study. Meta-analysis of GDF5 rs143383 polymorphism was statistically associated with increased risk of musculoskeletal degenerative diseases under each genetic model (allele model: OR = 1.32, 95% CI 1.19-1.48, P = 0.000; homozygote model: OR = 1.80, 95%CI 1.49-2.16, P = 0.000; heterozygote model: OR = 1.37, 95%CI 1.21-1.55, P = 0.000; dominant model: OR = 1.56, 95%CI 1.39-1.75, P = 0.000; recessive model: OR = 1.39, 95%CI 1.20-1.60, P = 0.000). Stratified analyses based on disease type showed a significant association between the GDF5 rs143383 polymorphism and increased risk of IDD and OA under all genetic models studied. When stratified with ethnicity, pooled outcomes revealed that this polymorphism was significantly related with increased risk of musculoskeletal degenerative diseases in both Asian and Caucasian populations under all genetic models studied. Conclusions The present study suggested that GDF5 rs143383 polymorphism was significantly associated with susceptibility to musculoskeletal degenerative diseases.